Regressing Dual Side of Motivation on Exercise Commitment in Adults: A Structured Equation Modelling Approach - Yan Zhou (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Physical activity and exercise is the key to a healthy lifestyle and prevention of disease. Lack of persistency and regular commitment towards exercise are the basic challenges that lead individuals to develop inactive physical lifestyles. Motivation for exercise plays an important role in maintaining healthy lifestyle habits, a pre-requisite a healthy ageing process in the future. In this context, the self-determination theory is a widely used theory in the context of studying the influence of an individual’s motivation for his/her behavior. In this context, the current study has been conducted with the objective to explore how autonomous, controlled and extrinsic motivation influences levels of exercise persistence and exercise commitment with the mediation of exercise enjoyment in China. To achieve this objective, the data was collected from 304 respondents through a survey questionnaire and the collected data was analyzed. The results obtained from the analysis have indicated that the impact of autonomous motivation is positively significant for exercise persistence but is insignificant in case of exercise commitment. Similarly, the impact of controlled motivation is significant and positive for both exercise commitment and persistence. Moreover, the impact of extrinsic motivation is negatively significant for both exercise commitment and persistence. Lastly, exercise enjoyment has significant mediating role between all the independent variables and dependent variables. The study has theoretical as well as practical implications, especially the gym trainers and physical health fitness coaches.